Enhancing Classroom Management Self-Efficacy through Teacher Professional Education Program: An Explorative Study - Purniningtyas, Annisaa; Endang Fauziati; Dewi Rochsantiningsih (Universitas Hamzanwadi, 2024)
Classroom Management Self-Efficacy (CMSE) is crucial for teachers to effectively manage diverse student needs, fostering preparedness, perseverance, and the ability to maintain a productive learning environment. This study examines how Indonesia’s Pendidikan Profesi Guru (PPG), or Teacher Professional Education program, enhances CMSE among certified English teachers. By exploring the experiences of three purposively selected junior high school teachers, this research highlights the role of professional development in building teaching confidence. Data were gathered through a validated CMSE scale, which assessed perceptions across various classroom management domains, and semi-structured interviews that provided rich qualitative insights. Using the interactive model by Miles, Huberman, and Saldana (2014), the analysis revealed two key findings: teachers with high CMSE consistently exhibited perseverance, motivation, and sociability—critical traits for effective classroom management—and participants credited the PPG program, particularly its structured components such as material deepening, learning device development, and teaching practice (PPL), with significantly improving their CMSE. These findings emphasize that well-designed professional development programs not only boost self-efficacy but also equip teachers with practical skills for managing classrooms effectively. The study concludes that sustained engagement in programs like PPG is vital for enhancing classroom management skills and offers valuable insights for shaping teacher education policies and practices to ensure continuous professional growth and improved teaching outcomes.